Fluoride Coatings on Magnesium Alloy Implants - ChuanYao Zhai; Chun Yu Dai; Xun Lv; Biying Shi; Yu Ru Li; Yifan Yang; Di Fan; Eui-Seok Lee; Yunhan Sun; Heng Bo Jiang (Bioinorganic Chemistry and Applications)
After several years of research and development, it has been reported that magnesium alloys can be used as degradable metals in some medical device applications. Over the years, fluoride coatings have received increasing research attention for improving the corrosion resistance of magnesium. In this paper, different methods for preparing fluoride coatings and the characteristics of these coatings are reported for the first time. The influence of the preparation conditions of fluoride coatings, including the magnesium substrate, voltage, and electrolyte, on the coatings is discussed. Various properties of magnesium fluoride coatings are also summarized, with an emphasis on corrosion resistance, mechanical properties, and biocompatibility. We screened experiments and papers that planned the application of magnesium fluoride coatings in living organisms. We have selected the literature with the aim of enhancing the performance of in vivo implants for reading and further detailed classification. The authors searched PubMed, SCOPUS, Web of Science, and other databases for 688 relevant papers published between 2005 and 2021, citing 105 of them. The selected time range is the last 16 years. Furthermore, this paper systematically discusses future prospects and challenges related to the application of magnesium fluoride coatings to medical products.